Q&A: The Upper Limit. - Hoffmann, Leah (Communications of the ACM, 2009)
An interview with professor Jeannette Wing is provided. Wing works with the study of abstraction, computer software specification and verification, and concurrent and distributed systems. Topics include her tenure at the National Science Foundation, her work on the Cluster Exploratory program, and her work in the area of computational thinking.